2019
DOI: 10.1080/10717544.2019.1693707
|View full text |Cite
|
Sign up to set email alerts
|

Development of dual-targeted nano-dandelion based on an oligomeric hyaluronic acid polymer targeting tumor-associated macrophages for combination therapy of non-small cell lung cancer

Abstract: (2019) Development of dual-targeted nano-dandelion based on an oligomeric hyaluronic acid polymer targeting tumor-associated macrophages for combination therapy of nonsmall cell lung cancer,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Nanodandelions can easily enter tumour tissue through the vascular barrier due to their small size. Effective antitumour activity and reduced side effects were confirmed in antitumour experiments in A549 tumour-bearing mice [ 150 ]. Sustained-release characteristics of NPs may aid the effectiveness of chemotherapy by maintaining drug concentrations at the tumour site for longer durations.…”
Section: Cancer Therapymentioning
confidence: 99%
“…Nanodandelions can easily enter tumour tissue through the vascular barrier due to their small size. Effective antitumour activity and reduced side effects were confirmed in antitumour experiments in A549 tumour-bearing mice [ 150 ]. Sustained-release characteristics of NPs may aid the effectiveness of chemotherapy by maintaining drug concentrations at the tumour site for longer durations.…”
Section: Cancer Therapymentioning
confidence: 99%
“…Recently, the HA-based nanoparticles were employed to deliver herbal extracts so as to promote cancer immunotherapy. Wang et al [ 274 ] developed quercetin-dithiodipropionic acid-oligomeric hyaluronic acid-mannose-ferulic acid (Que-S-S-oHA- Man-FA, QHMF) to form dandelion-like nanomicelles for delivering both curcumin and baicalin into tumor tissues. They demonstrated that these drug-loaded nanomicelles could easily penetrate through vascular barriers and enter tumor tissues.…”
Section: Hyaluronic Acid-based Nanomedicinesmentioning
confidence: 99%
“…A similar micellar delivery system, encapsulating CUR and baicalin, was found to induce macrophage remodeling towards a tumor-suppressive phenotype (B. Wang et al, 2019), while dendrosomal nano-CUR induced macrophage switching from the M2 phenotype to the M1 phenotype (Shiri et al, 2015). A dual-pH-sensitive polymeric nanodrug carrying an anti-PD-1 antibody on the shell and CUR in the core was developed by Xiao et al (Z. Xiao et al, 2020).…”
Section: Non-flavonoidsmentioning
confidence: 99%